1997
DOI: 10.1016/s0014-5793(96)01505-0
|View full text |Cite
|
Sign up to set email alerts
|

Non‐thermal effects of microwaves on proteins: thermophilic enzymes as model system

Abstract: Two thermophilic and thermostable enzymes, isolated from Sulfolohus solfataricus, S-adenosylhomocysteine hydrolase and 5'-methylthioadenosine phosphorylase, were exposed to 10.4 GHz microwave radiation in order to discriminate between thermal and non-thermal microwave effects. The exposure causes a non-thermal, irreversible and time-dependent inactivation of both enzymes; the inactivation rate is related to the energy absorbed and is independent of the enzyme concentration. The influence of salts on enzyme ina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
81
1
4

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 188 publications
(91 citation statements)
references
References 29 publications
5
81
1
4
Order By: Relevance
“…Thermal denaturation using a microwave promotes an unmasking effect as it disrupts the secondary and tertiary structure of the proteins 6 . Other mechanisms have been proposed including molecular rapid oscillation 6,10,11 . Thus, boiling in the citric acid and tri-sodium citrate buffer is a key step in antigen-retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal denaturation using a microwave promotes an unmasking effect as it disrupts the secondary and tertiary structure of the proteins 6 . Other mechanisms have been proposed including molecular rapid oscillation 6,10,11 . Thus, boiling in the citric acid and tri-sodium citrate buffer is a key step in antigen-retrieval.…”
Section: Discussionmentioning
confidence: 99%
“…Hopwood et al [11] concluded that MW irradiation did not produce cleavage or polymerization of proteins and irradiation resulted in an electrophoretic pattern that was similar to that obtained when lysozyme and hemoglobin was heated in formaldehyde to 60°C for 30 min. Interestingly, Porcelli et al [33], more recently, showed results to the contrary. In a study of Sadenosylhomocysteine hydrolase and 5'-methylthioadenosine phosphorylase, two thermophilic and thermostable enzymes, they found that exposure to MWs caused a nonthermal, irreversible and time-dependent inactivation of both enzymes.…”
Section: Discussionmentioning
confidence: 94%
“…temperature and holding time; and 3) the existence of nonthermal effect from the microwave heating. 27), 36) Shown in Fig. 3 are FESEM images of the asreceived ZrO 2 powders and CaZrO 3 powders prepared by MMSS.…”
Section: Characterization Of Cazro 3 Powdersmentioning
confidence: 99%